Use of Patented Traditional Chinese Medicine against COVID-19 A Practical Manual - Zhai, Huaqiang; Wang, Yanping; Yang, Yiheng; Li, Xiaodong; Shao, Yingjun (World Scientific Publishing Co., 2021)
COVID-19 is a severe and complex epidemic ravaging many countries. Traditional Chinese medicine (TCM) has accumulated rich experience and achieved outstanding effects in its struggle against epidemics for thousands of years. As an essential intervention means for prevention and control of COVID-19, TCM boasts significant effects in relieving fever symptoms, slowing down disease progression, preventing disease transformation, reducing hormone dosage, and alleviating complications. Establishing and improving the emergency supply service mode of Chinese medicine in response to public health emergencies, and scientifically managing and allocating Chinese medicine medical resources are conducive to establishing a green channel for the emergency supply of Chinese medicine in response to major public health emergencies. This book focuses on the four oral Chinese patent medicines used in the clinical treatment period based on the Guidelines for the Diagnosis and Treatment of COVID-19 by the National Health Commission and National Administration of Traditional Chinese Medicine of China. This work is not only an important part of the theoretical system of TCM treatment based on syndrome differentiation but also an effective way to promote an even deeper integration of clinical pharmaceutical service and clinical medical practice.